Women and Power in Early Islamic History: Jawari of the Abbasid Court (786-861 AD) - Hannan, Haukil; Syaie, Akhmad Najibul Khairi (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
The significant presence of jawari owned by the caliphs of Islam became a phenomenon during the early period (170 AH/ 786 AD-247 AH/861 AD) of Abbasid rule. This article aims to examine why the early Abbasid rulers (786-861 AD) "kept" many jawari in their palaces and whether they had relations with all of them. Through a historical and sociological approach, the findings of this study indicate that the large number of jawari owned by the Abbasid caliphs during the early period was closely related to the advancements (economic, social, and political) achieved by the Abbasids at that time; the acceptance of slavery in Islam, territorial expansion (futuhat), the growth of economic trade sectors, the flourishing of entertainment in society, and the influence of Ctesiphon. Furthermore, the ownership of a large number of jawari did not necessarily indicate strong sexual desires of the caliphs; rather, it primarily served as a symbol of power, as evidenced by the fact that only individuals with significant authority typically possessed numerous jawari. This was also supported by a strong tradition of rewarding enslaved individuals as gifts, and the fact that not all Jariyah were intimate with their masters.